1999
DOI: 10.1292/jvms.61.897
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Canine Oral Epulides.

Abstract: ABSTRACT. To clarify the clinicopathological features of canine epulides, 189 epulides were reviewed retrospectively. The incidence of the fibromatous, ossifying, acanthomatous and giant cell epulides were 56.6% (107/189), 23.3% (44/189), 18.0% (34/189) and 2.1% (4/189), respectively. The average ages of dogs with fibromatous, ossifying, acanthomatous and giant cell epulides were 8. 8, 8.4, 7.8 and 8.7 years, respectively. The male/female ratio of dogs with the acanthomatous epulis (0.8) was lower than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
46
2
16

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 12 publications
7
46
2
16
Order By: Relevance
“…8,10 International, multicenter studies would be preferable in order to establish which breeds are predisposed to oral neoplasms. This problem is illustrated by the differences in breed distribution between our material and that of other investigators.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…8,10 International, multicenter studies would be preferable in order to establish which breeds are predisposed to oral neoplasms. This problem is illustrated by the differences in breed distribution between our material and that of other investigators.…”
Section: Figurementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The first survey of both neoplastic and non-neoplastic oropharyngeal lesions in domestic animals reported that 20 % of all canine oral lesions were non-neoplastic, 39 % benign neoplasms, and 41 % malignant neoplasms. [1][2][3][4][5][6][7][8][9][10] The first survey of both neoplastic and non-neoplastic oropharyngeal lesions in domestic animals reported that 20 % of all canine oral lesions were non-neoplastic, 39 % benign neoplasms, and 41 % malignant neoplasms.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,13,17,18,21,22,25 Although human peripheral giant cell granulomas are generally considered reactive and non-neoplastic, the cause of these lesions is poorly understood. 13,17,18 Six reported cases of canine peripheral giant cell granuloma did not recur after surgical excision.…”
mentioning
confidence: 99%
“…4 Giant cell epulides are both clinically and pathologically less well characterized but exhibit an aggressive clinical course and are, unlike in dogs, reported to recur after surgery. 19,28 Because of the resemblance of the MGCs to foreign body-type giant cells, the giant cell epulis sometimes is considered to represent a reactive giant cell-rich granulomatous lesion, but the real origin remains unknown. 19,21 In human oral cavity proliferations containing MGCs, like the central and peripheral giant cell granuloma, MGCs have been considered as phagocytes, 12 foreign body cells, 24 or osteoclasts.…”
mentioning
confidence: 99%